Clinical Features and Prevalence of Spondyloarthritis in a Cohort of Italian Patients Presenting with Acute Nongranulomatous Anterior Uveitis - Elena Bolletta; Pierluigi Macchioni; Giorgia Citriniti; Valentina Mastrofilippo; Raffaella Aldigeri; Luca De Simone; Fabrizio Gozzi; Chantal Adani; Anna Sangiovanni; Chiara Posarelli; Michele Figus; Francesco Muratore; et al. (Journal of Immunology Research)
Purpose. To describe the clinical features of acute nongranulomatous anterior uveitis (NGAU) patients and to estimate the prevalence of concomitant spondyloarthritis (SpA). Methods. Retrospective study of consecutive patients affected by NGAU referred to the Ocular Immunology Unit of the AUSL-IRCCS di Reggio Emilia, Italy, between January 2016 and January 2019. All patients underwent ophthalmic evaluation and blood test with HLA-B27 typing and were referred to a rheumatologist to identify any undiagnosed SpA. SpA was classified according to the Assessment of SpondyloArthritis international Society (ASAS) criteria in axial or peripheral SpA. Patients were divided into two groups: NGAU with associated SpA (SpA+) and NGAU without SpA (SpA-). Clinical and demographic features of the two groups, including sex, HLA-B27, family history of rheumatic disease, uveitis laterality, course, and severity of ocular inflammation, complications, and treatment, were compared. Results. Ninety-nine patients with NGAU were enrolled, of whom 36 (36%) with a diagnosis of SpA: 14 with peripheral SpA and 22 with axial SpA. The prevalence of SpA was higher in HLA-B27-positive patients than in HLA-B27-negative patients (50% vs. 15%, p<0.0001). The multivariate logistic regression (R2=0.28) for SpA diagnosis identified as significant predictive factors: age at diagnosis (odds ratio OR=0.95, 95% confidence interval [CI]: 0.91-0.99) and HLA-B27+ (OR=5.32, 95% CI: 1.80-15.70). Conclusions. Our results confirmed the high prevalence of undiagnosed SpA in patients with NGAU, suggesting that, regardless of HLA-B27 status, in the presence of IBP and/or peripheral arthritis, patients with NGAU must be referred to the rheumatologist to allow earlier diagnosis.